The influence of chemistr.io on chemical bonding education: a quantitative analysis - Mohd Ali, Noor Saadiah; Mat Russ, Nazirah; Jamaudin, Rosmaya; Mat Zaid, Muhammad Afham Fakhri; Che Rahimi, Che Azim Hakimi; Muhamad Nizam, Anwar Razeeq (ASIAN SCHOLARS NETWORK, 2025)
Gamification approach has become a popular method of engaging students in the learning process across all levels of education and disciplines, including chemistry. Chemistry is often considered a challenging subject because it involves complex concepts and understanding how they relate to one another. This study addresses the challenges faced by learners, especially pre-university students, in grasping abstract chemical bonding theories through traditional pedagogical methods. Thus, a mobile game-based called Chemistr.io was developed and incorporated with assessment that tailored with one of the topics in Physical Chemistry, namely Chemical Bonding. The gamification approach was evaluated based on overall feedback towards the gamification element of Chemistr.io quantitatively, using a 5-point numerical rating scale. The data collected from the chemistry students were then analysed descriptively using mean value, combined with PLS-SEM. The results revealed that students engaged in these gamification activities demonstrated positive and a deeper grasp of the subject matter with the t > 1.96 and p ≤ 0.05. Incorporating gamification into Chemistry could leverage motivation and critical thinking in the subject matter. The Chemistr.io mobile game can be commercialized further and serve as an interactive learning module for Physical Chemistry subjects.